A randomised trial comparing the efficacy and safety of topical ketoprofen in Transfersome® gel (IDEA-033) with oral ketoprofen and drug-free ultra-deformable Sequessome™ vesicles (TDT 064) for the treatment of muscle soreness following exercise. Issue 1 (2nd January 2016) - Seidel, Egbert J.; Rother, Matthias; Regenspurger, Katja; Rother, Ilka
Abstract: We compared the effectiveness of topical ketoprofen in Transfersome ® gel (IDEA-033) with oral ketoprofen and drug-free Sequessome™ vesicles (FLEXISEQ ® Sport; TDT 064) in reducing calf muscle soreness. One hundred and sixty eight healthy individuals with a pain score ≥3 (10-point scale) 12–16 h post-exercise (walking down stairs with an altitude of 300–400 m) were randomised to receive IDEA-033 plus oral placebo (two dose groups), oral ketoprofen plus TDT 064, or TDT 064 plus oral placebo. The primary endpoint was muscle soreness reduction from pre-dosing to Day 7. Higher pain scores were recorded with oral ketoprofen plus TDT 064 (mean ± s 462.4 ± 160.4) versus IDEA-033 plus oral placebo (434.7 ± 190.8; P = 0.2931) or TDT 064 plus oral placebo (376.2 ± 159.1; P = 0.0240) in the 7 days post-exercise. Recovery from muscle soreness was longer with oral ketoprofen plus TDT 064 (mean 91.0 ± 19.5 h) versus IDEA-033 plus placebo (mean 81.4 ± 22.9 h; P = 0.5964) or TDT 064 plus placebo (mean 78.9 ± 22.8 h; P = 0.0262). In conclusion, ultradeformable phospholipid vesicles ± ketoprofen did not retard recovery from muscle soreness. TDT 064 improves osteoarthritis-related pain and could be of interest as a treatment for joint pain during and post-exercise.